Ulnar Nerve Transposition at the Elbow under Local Anesthesia: A Patient Satisfaction Study - del Vecchio, Pietro M. Roberti; Christen, Thierry; Raffoul, Wassim; Erba, Paolo (Journal of Reconstructive Microsurgery, 2015)
Background Ulnar nerve decompression at the elbow traditionally requires regional or general anesthesia. We wished to assess the feasibility of performing ulnar nerve decompression and transposition at the elbow under local anesthesia.Methods We examined retrospectively the charts of 50 consecutive patients having undergone ulnar nerve entrapment surgery either under general or local anesthesia. Patients were asked to estimate pain on postoperative days 1 and 7 and satisfaction was assessed at 1 year.Results On day 1, pain was comparable among all groups. On day 7, pain scores were twice as high when transposition was performed under general anesthesia when compared with local anesthesia. Patient satisfaction was slightly increased in the local anesthesia group. These patients were significantly more willing to repeat the surgery.Conclusion Ulnar nerve decompression and transposition at the elbow can be performed under local anesthesia without added morbidity when compared with general anesthesia.
Keywords: general anesthesia; local anesthesia; transposition; ulnar nerve